Conceptual knowledge relationship model of enterprise architecture and top management roles - Ahmad @ Abdul Mutalib, Hawa; Ahmad, Aishah; Nik Abdullah Haffaz, Nik Hazliana (Adelaide, Australia, 2015)
Enterprise Architecture (EA) continues to gain global recognition as a management tool that would improve the organization’s performance. The literature review reveals that the alignment of EA with that of the business strategy was not achieved due to inadequate EA knowledge at Top Management (TM) level. This study aims to gauge the level of EA knowledge required at TM level to enable the creation of EA that would enable the alignment of strategic business vision with that of EA. A semistructured interview was conducted with several personnel in an organization. Data were analyzed using the constant comparative method. This study identified that the TM need to have understanding to two sets of EA knowledge, viz, business process management (BPM) and technology knowledge. A conceptual knowledge relationship model is proposed through synthesizing the roles of EA and TM in supporting the TM in identifying the EA knowledge required. The findings gave contribution to academicians and practitioners with knowledge of how to improve EA assimilation and a structured roadmap for understanding EA to achieve high business value.